WISP1 induces ovarian cancer via the IGF1/αvβ3/Wnt axis - Yan Li; Fangfang Wang; Tianyi Liu; Nan Lv; Xiaolei Yuan; Peiling Li (BMC, 2022)
Abstract Background This study intended to clarify the mechanisms by which WISP1-mediated IGF1/αvβ3/Wnt axis might affect the progression of ovarian cancer. Methods Bioinformatics analysis was implemented for pinpointing expression of IGF1 and WISP1 which was verified through expression determination in clinical tissue samples and cells. Next, gain- or loss-of-function experimentations were implemented for testing CAOV4 and SKOV3 cell biological processes. The interaction between WISP1 and IGF1 was verified by co-immunoprecipitation and the molecular mechanism was analyzed. Finally, ovarian cancer nude mouse models were prepared to unveil the in vivo effects of WISP1/IGF1. Results IGF1 and WISP1 expression was elevated in ovarian cancer tissues and cells, which shared correlation with poor prognosis of ovarian cancer sufferers. Elevated IGF1 induced malignant properties of ovarian cancer cells through activation of PI3K-Akt and Wnt signaling pathway. WISP1 was positively correlated with IGF1. WISP1 could enhance the interaction between IGF1 and αvβ3 to induce epithelial-mesenchymal transition. In vivo experiments also confirmed that upregulated WISP1/IGF1 induced tumorigenesis and metastasis of ovarian cancer cells. Conclusion In conclusion, WISP1 can facilitate ovarian cancer by activating Wnt via the interaction between IGF1 and αvβ3.